Diversity of Karyolysus and Schellackia from the Iberian lizard Lacerta schreiberi with sequence data from engorged ticks - Zechmeisterová, Kristína; Goüy de Bellocq, Joëlle; Široký, Pavel (Parasitology, 2019)
Apicomplexan haemoparasites of the genera Schellackia Reichenow, 1919, and Karyolysus Labbé, 1894, seem to be common in lizards and widespread across the world. For decades, their identification has been based on morphological descriptions and life cycle patterns, with molecular characterizations, applied only recently. We used molecular characterization to confirm the identification of haemoparasites detected by microscopy in blood smears of Lacerta schreiberi Bedriaga, 1878, a lizard of the Iberian Peninsula. Since blood samples other than blood smears were not available from the studied lizards, 264 engorged ticks Ixodes ricinus (Linneaus, 1758) collected from them were used as an alternative non-invasive source of haemoparasite DNA for molecular genetic analyses. Of the 48 blood smears microscopically examined, 31 were positive for blood parasites (64.6% prevalence). We identified trophozoites and gamonts similar to Karyolysus lacazei (Labbé, 1894) (24/48; 50%) and Schellackia-like sporozoites (20/48; 41.7%). Mixed infections with both species occurred in 13 blood smears (27.1%). Sequence data were obtained for both parasites from engorged ticks. Phylogenetic analyses placed our unique haemogregarine sequence within the Karyolysus clade, nevertheless, within substantial polytomy. Thus, according to its morphology and effect on the host cell, we refer to this haemogregarine as Karyolysus cf. lacazei. Besides the Schellackia sequences being identical to a previously identified haplotype, we also obtained sequences of three new closely related haplotypes.
Keywords: Sporozoites; Animals; Eucoccidiida; trofozoiti; Trophozoites; klíště; kokcidióza; Coccidiosis; Genetic Variation; Phylogeny; DNA, Protozoan; sporozoiti; Haplotypes; protozoální DNA; Lizards; Sequence Analysis, DNA; ještěři; zvířata; haplotypy; sekvenční analýza DNA; fylogeneze; genetická variace; Ixodes